Fixed-time distributed formation control for nonlinear heterogeneous multiagent systems subject to input nonlinearities and actuator faults - Jiao, Jianmin; Li, Junmin; He, Chao; Zhang, Rui (Nonlinear Analysis: Modelling and Control, 2026)
This work focuses on distributed practical fixed-time formation (PFTF) control for heterogeneous multiagent systems (MASs) with inherent nonlinear dynamics, coupled input nonlinearities, and potential actuator faults. Conventional backstepping methods face the challenge of “differential explosion”. To resolve this issue, we propose an innovative command filtering strategy with fixed-time convergence properties, integrated with a compensating mechanism that also ensures fixed-time suppression of filtering errors. Leveraging the synergy of fixed-time control theory, backstepping recursion, and neural networks function approximation, a distributed PFTF control protocol is developed. The designed scheme ensures that the MASs attain the predefined formation configuration within a fixed time, while driving all errors converge to a small residual set. Numerical simulations validate the effectiveness and performance of the proposed approach.